Placental Pathology in Severe Pre-eclampsia and Eclampsia (Nepalese Medical Journal, 2018)
Introduction: Hypertensive disorders complicating pregnancy contribute significantly to maternal and perinatal morbidity and mortality. Since placenta is the functional unit between the mother and fetus examination of placenta can give an idea about prenatal experience of fetus. The aim is to observe the morphology and histopathology of placenta in pregnancy with severe preeclampsia / eclampsia between 20-42 weeks of gestation.Materials and Methods: This was a prospective, descriptive study carried out in the Department of Obstetrics and Gynaecology and Department of Pathology at Institute of Medicine, Tribhuwan University Teaching Hospital, TUTH for one year, starting from 15th May 2015 - 14th May 2016. A total 55 placentas, 48 of severe preeclampsia and 7 of eclampsia were collected and placental morphometric parameters, gross and histopathological features were examined.Results: It was found that placental morphometric parameters were significantly reduced. Histopathological study showed significant number of syncytial knots, areas of fibrinoid necrosis, hyalinization and calcification. These placental findings were associated with significantly decreased weight of fetus at birth.Conclusions: Preeclampsia and eclampsia cause significant placental morphometric and histological changes which in turn adversely affects neonatal birth weight.Nepalese Medical Journal, vol.1, No. 1, 2018, page: 32-35